Mixed-mode fracture characterization of fine aggregate mixtures using semicircular bend fracture test and extended finite element modeling. (30th December 2015) - Ban, Hoki; Im, Soohyok; Kim, Yong-Rak
Highlights: Integrated experimental-computational effort to characterize mixed-mode fracture. Semicircular bend fracture tests integrated with the extended finite element model. The extended finite element model with a mode-dependent cohesive zone fracture. Much larger fracture toughness of in-plane shear mode-II than opening mode-I. A power relationship between the total fracture toughness and involvement of in-plane shear mode-II fracture in the total. Abstract: This paper presents integrated experimental-computational efforts to characterize the mixed-mode fracture of a fine aggregate matrix mixture which is the primary phase of cracks around stiffer coarse aggregates when typical asphalt concrete mixtures are subjected to intermediate service temperatures. Experimentally, semicircular bend fracture tests were conducted by varying the geometric-loading configurations with different initial notch inclination angles and supporting spans to achieve different fracture modes (opening mode-I, in-plane shear mode-II, and mixed). The semicircular bend fracture test results were then integrated with the extended finite element model which is also incorporated with mode-dependent cohesive zone fracture to properly identify the mode-dependent fracture properties. The test and model simulation results indicated that the cohesive zone fracture toughness of in-plane shear mode-II is quite different (approximately three times greater) from opening mode-I fracture toughness. The critical fracture energy was related to the mixed-mode ratio, which presented a power relationship between the total fracture toughness and involvement of in-plane shear mode-II fracture in the total. Findings and observations from this study, although they are limited at this stage, imply that the mixed-mode fracture characteristics are significant and need to be considered in the structural design of asphalt pavements with which multi-axial cracking is usually associated.